Principi, approcci e applicazioni della biblioteconomia comparata Una proposta per nuovi percorsi di ricerca - Bilotta, Anna (Biblioteche & bibliotecari / Libraries & librarians, 2022)
The book identifies the characteristics of comparative method in the social sciences and its applications in library and information science, analyzing aims, methodological problems, phases and approaches of comparative librarianship. It is a disciplinary field, still little explored in the Italian context, which aims to examine structures, services, practices and functions of libraries to highlight aspects and peculiarities in a defined context, relating different realities, analyzing causes and effects of emerged specificities and evaluating factors that influence their development. The reflection is enriched by a critical analysis of Italian and foreign comparative researches and by the proposal of a work outline to approach comparative librarianship.